Evaluasi perpindahan panas dan efisiensi superheater pada unit multi fuel boiler - Panjaitan, J.R.H.; Sihotang, J.S.; Sirait, K.M.; Pakpaha, R. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
The heat exchanger was used to carry out the heat exchange process between two fluids. One of the heat exchangers is the Multi Fuel Boiler. In multi-fuel boilers, there was a superheater which functions to convert saturated steam into dry steam. In this research, the evaluation of superheater heat transfer efficiency in Multi Fuel Boiler Units will be studied. The results showed that the highest heat transfer coefficient for the superheater was on day 6 at 141,942.81 W/m2K with 56.51% efficiency. Meanwhile, the highest superheater efficiency was 58.72% on day-7 with the heat transfer coefficient being 130,755.76 W/m2K. Factors such as steam temperature, flue gas temperature, steam and flue gas flow rate, heat transfer area and soot blower influence the heat transfer coefficient and efficiency of the superheater.